Work personality types and pre-service mathematics teachers' reasons for choosing mathematics teaching - Akkurt, Şeyma. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The present study aims to investigate the personality types and the reasons of Turkish pre-service mathematics teachers for choosing mathematics teaching and examines differences according to gender and level of teaching of the participants. It is also aimed to determine if there is a relationship between the personality types and reasons for choosing mathematics teaching. The participants of this study are 384 senior pre-service mathematics teachers from 9 universities in Turkey. The aim of the present study was threefold. First one was to examine the reasons given by Turkish pre-service mathematics teachers for choosing teaching as a career through demographic characteristics (gender and level of teaching) of the participants. Among participants, altruistic social utility reasons (enhance social equity, make social contribution, and shape future of children and adolescents) was the highest rated category of reasons. On the other hand, the fallback reason category was rated lowest. The second purpose was to examine the work personality types of Turkish pre-service mathematics teachers based on Holland’s (1997) work personality types theory through demographic characters (gender and level of teaching). Social personality type category was rated highest which is consistent with the theory. Investigative work personality type was rated second highest while the enterprising category was rated lowest. The analysis showed that, women have significantly higher scores on artistic work personality type, while men have significantly higher score on realistic work personality type. Moreover, secondary mathematics pre-service teachers have significantly higher score on investigative work personality type compared to primary pre-service mathematics teachers. The third aim was to determine if there is a relationship between the reasons and work personality types of the Turkish pre-service mathematics teachers. Social utility values reasons were found to be highly related with social work personality type.
Keywords: Mathematics teachers.